Air conditioning study for automotive application / Alauddin Hafiz Yusof - Alauddin Hafiz, Yusof (2008)
Air conditioning is a process by which air is cooled or heated, cleaned or filtered, and circulated or recirculated. Air conditioning had become a standard option on most vehicle for enhancing comfort and safety. Most of automotives air conditioning system, the compressor is a belt-driven coupled to the engine. This means the cycling rate is directly related to the engine speed. Based on the situation, the air conditioning test rig was built to understand clearly about the air conditioning system including the vapor compression refrigeration cycle in the system and the function of each component in the system. There are four locations of temperature measurement were selected in order to develop the test rig. These locations are at the inlet and outlet of the compressor, the outlet of the condenser, and the inlet of the evaporator, respectively. The pressure was measured at the low pressure side and high pressure side which are at the outlet of the evaporator and inlet of the condenser, respectively. All of the parameters are measured during the cycle and were analyzed by using the properties table for refrigerant-134a and the p-h diagram for refrigerant-134a in order to determine the heat rejection, cooling effect, work of compressor and the coefficient of performance (COP) of the air conditioning system. The refrigerant mass flow rate was calculated based on the theory calculation. The heat rejection, cooling effect, work of compressor, refrigerant mass flow rate, and the COP of the air conditioning system were investigated at variable speed of compressor. The COP of the system was decreasing as the increasing of the compressor speed. The COP of the system at the compressor speed of 1500 rpm is 13.48 and was decreasing to the value of 10.33, 7.82, and 6.53 when the compressor speed was increasing to 2000 rpm, 2500 rpm, and 3000 rpm, respectively.